Specific Localization and Quantification of the Oligo‐Mouse‐Microbiota (OMM12) by Fluorescence In Situ Hybridization (FISH). Issue 9 (12th September 2022) - Brugiroux, Sandrine; Berry, David; Ring, Diana; Barnich, Nicolas; Daims, Holger; Stecher, Bärbel
Abstract: The oligo‐mouse‐microbiota (OMM 12 ) is a widely used syncom that colonizes gnotobiotic mice in a stable manner. It provides several fundamental functions to its murine host, including colonization resistance against enteric pathogens. Here, we designed and validated specific fluorescence in situ hybridization (FISH) probes to detect and quantify OMM 12 strains on intestinal tissue cross sections. 16S rRNA‒specific probes were designed, and specificity was validated on fixed pure cultures. A hybridization protocol was optimized for sensitive detection of the individual bacterial cells in cryosections. Using this method, we showed that the intestinal mucosal niche of Akkermansia muciniphila can be influenced by global gut microbial community context. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Localization and quantification of OMM 12 single strains in mouse cecum cross section Support Protocol : Establishment of specific FISH probe set for OMM 12 syncom